A survey of patient perceptions of tele-epilepsy services in north queensland. Issue 5 (8th May 2017) - Adamson, Sarah; Smit, Michelle; Costello, Craig
Abstract : Objectives: To compare patient satisfaction and perception of tele-epilepsy versus face-to-face consultations in North Queensland. Methods: A questionnaire was completed by consecutive epilepsy patients following consultant neurologist assessment in Townsville, Queensland between October 2013 and October 2014. Telehealth consults were conducted by videoconference between the neurologist and the patient with their local GP/hospital. Questions were answered on a scale of 1 (strongly disagree) to 5 (strongly agree). Results: Sixty-eight surveys were completed; 49 face-to-face and 19 telehealth, with three patients completing both. While the face-to-face group scored significantly greater satisfaction (mean total score 48.91/50, SD 2.54) compared with the telehealth group (mean 46/50, SD 4.95), the absolute difference was low, likely reflective of different numbers in each group. Cumulative scoring of favourable outcomes (strongly agreed, agreed, neutral) demonstrated that all tele-epilepsy patients indicated satisfaction with care provided by the consultant with the help of local staff (84.2%, 10.5% and 5.3%, respectively) and none of the tele-epilepsy patients reported difficulty seeing the doctor through video (89.5%, 10.5%). All telehealth consulted patients reported that the telehealth model saved them time and money. Nearly all (94.7%: 68.4%, 10.5% and 15.8%) of tele-epilepsy patients indicated preference for further video consultation rather than travel for in person attendance. Conclusions: Despite significantly higher face-to-face patient satisfaction, tele-epilepsy patients reported high levels of satisfaction with the tele-epilepsy model of care. As such, tele-epilepsy is a viable model for the delivery of epileptic care within regional settings. Our study was not focused on outcomes or efficacy therefore further research is needed on whether tele-epilepsy provides equal outcomes in care.